Npl3 stabilizes R‐loops at telomeres to prevent accelerated replicative senescence. (6th February 2020) - Pérez‐Martínez, Lara; Öztürk, Merve; Butter, Falk; Luke, Brian
Abstract: Telomere shortening rates must be regulated to prevent premature replicative senescence. TERRA R‐loops become stabilized at critically short telomeres to promote their elongation through homology‐directed repair (HDR), thereby counteracting senescence onset. Using a non‐bias proteomic approach to detect telomere binding factors, we identified Npl3, an RNA‐binding protein previously implicated in multiple RNA biogenesis processes. Using chromatin immunoprecipitation and RNA immunoprecipitation, we demonstrate that Npl3 interacts with TERRA and telomeres. Furthermore, we show that Npl3 associates with telomeres in an R‐loop‐dependent manner, as changes in R‐loop levels, for example, at short telomeres, modulate the recruitment of Npl3 to chromosome ends. Through a series of genetic and biochemical approaches, we reveal that Npl3 binds to TERRA and stabilizes R‐loops at short telomeres, which in turn promotes HDR and prevents premature replicative senescence onset. This may have implications for diseases associated with excessive telomere shortening. Synopsis: Npl3 interacts with telomeres through TERRA and RNA‐DNA hybrids. By stabilizing RNA‐DNA hybrids at short telomeres Npl3 drives telomere recombination and prevents accelerated senescence. Npl3 is an RNA binding protein that associates with telomeres. Npl3 binds telomeres via TERRA and RNA‐DNA hybrids. R‐loops are stabilized by Npl3 at short telomeres. Npl3 promotes recombination to prevent premature senescence. Abstract : Npl3 interacts with telomeres through TERRA and RNA‐DNA hybrids. By stabilizing RNA‐DNA hybrids at short telomeres Npl3 drives telomere recombination and prevents accelerated senescence.